DEM modelling of the activation and reactivation of capable faults in a typical Apulian rock succession: the viewpoint of local seismic effect during the 1948 Earthquake (Apulia, Italy) - Giovanni Bruno; Laura Guerra (Studia Geotechnica et Mechanica)
The extension and magnitude of deformations induced by the fault ruptures, especially in active and capable faults, have a significant impact on the integrity of anthropogenic surface structures and the way water and pollutants migrate underground. The purposes of this study are twofold. The first is to delineate the rupture mechanisms, the location and extent of the damage zone associated with the type of fault considered. The second is to assess the magnitude of coseismic displacements and local seismic response (LSR), in the case of surface propagation of a pre-existing active and capable normal fault. In previous studies, the lithotypes modelled had homogeneous and isotropic geotechnical behaviour unlike the lithoid and anisotropic lithotypes used in the present study. In addition, they used a generic time history of accelerations for the dynamic analyses that are non-seismocompatible to the expected seismicity in the case study geological–structural context.